Wellbeing of Transnational Muslim Families Marriage, Law and Gender - Tiilikainen, Marja; Al-Sharmani, Mulki; Mustasaari, Sanna (Taylor & Francis, 2019)
This book examines the needs, aspirations, strategies, and challenges of transnational Muslim migrants in Europe with regard to family practices such as marriage, divorce, and parenting. Critically re-conceptualizing 'wellbeing' and unpacking its multiple dimensions in the context of Muslim families, it investigates how migrants make sense of and draw on different norms, laws, and regimes of knowledge as they navigate different aspects of family relations and life in a transnational social space.